2019
DOI: 10.18203/2394-6040.ijcmph20191842
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of TORCH infection among pregnant women

Abstract: Background: TORCH infection complex during pregnancy has bad obstetric outcomes starting from low birth weight to congenital anomalies, sensory neural deafness, mental retardation, cerebral palsy and sometimes to fatal outcomes like abortion and still birth. As these diseases remain mostly asymptomatic these are rarely tested during pregnancy. Serology is the mainstay of diagnosing these infections..Methods: A cross sectional study was undertaken to estimate the burden of these infections in a rural belt of we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
0
5
1
3
Order By: Relevance
“…Anti-Rubella IgM was found as 1% (63/6306) in the evaluation of Rubella seroprevalence in our study. Anti-Rubella IgM seroprevalence positivity ranges between 0.2% and 2.25% as seen in 13). When Cetinkaya et al evaluated the data of 90988 patients in 26 studies conducted in our country, this rate was reported as 0.78% (17).…”
Section: Discussionmentioning
confidence: 84%
“…Anti-Rubella IgM was found as 1% (63/6306) in the evaluation of Rubella seroprevalence in our study. Anti-Rubella IgM seroprevalence positivity ranges between 0.2% and 2.25% as seen in 13). When Cetinkaya et al evaluated the data of 90988 patients in 26 studies conducted in our country, this rate was reported as 0.78% (17).…”
Section: Discussionmentioning
confidence: 84%
“…Dünyada yapılmış olan çeşitli çalışmalarda ise anti-T. gondii IgM pozitifliği %0.3-%13.3 aralığında anti-T.gondii IgG pozitifliği %1.71-%38.3 aralığında saptanmış olup bizim çalışmamıza benzer veriler elde edilmiştir. Anti-rubella IgM pozitifliği ise %0.5-%3 aralığında, anti-rubella IgG pozitifliği %68.4-%81.97 aralığında saptanmış olup; anti-CMV IgM pozitifliği %0.52-%1.8 aralığında, anti-CMV IgG pozitifliği ise %57.2-%95.09 aralığında saptanmış olup bizim çalışmamıza benzer veriler elde edilmiştir (36)(37)(38) .…”
Section: Discussionunclassified
“…The prevalence of TORCH infection varies geographically. 3,4,5,6 To the best of our knowledge, baseline data on seropositivity is not available from this part of Haryana.…”
Section: Introductionmentioning
confidence: 99%